2021
DOI: 10.1091/mbc.e20-05-0321
|View full text |Cite
|
Sign up to set email alerts
|

APC regulation of ESRP1 and p120-catenin isoforms in colorectal cancer cells

Abstract: The APC tumor suppressor protein is associated with the regulation of Wnt signaling, however APC also controls other cellular processes including the regulation of cell adhesion and migration. The expression of full-length APC in SW480 colorectal cancer cells (SW480+APC) not only reduces Wnt signaling, but increases membrane E-cadherin and restores cell-cell adhesion. This report describes the effects of full-length, wild-type APC (fl-APC) on cell-cell adhesion genes and p120-catenin isoform switching in SW480… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 62 publications
3
9
0
Order By: Relevance
“…This is consistent with results from previous research (Popescu et al, 2021). The high APC mutation in LCC suggests that it may be related to the inactivation of the Wnt pathway (Faux et al, 2021). LINC02418 has been shown to be a tumor driver in colon cancer (Tian et al, 2020), and whether there is an inherent relationship between LINC02418 and the mutated gene has not been investigated.…”
Section: Single Gene Mutation Landscape In Lcc and Rccsupporting
confidence: 90%
“…This is consistent with results from previous research (Popescu et al, 2021). The high APC mutation in LCC suggests that it may be related to the inactivation of the Wnt pathway (Faux et al, 2021). LINC02418 has been shown to be a tumor driver in colon cancer (Tian et al, 2020), and whether there is an inherent relationship between LINC02418 and the mutated gene has not been investigated.…”
Section: Single Gene Mutation Landscape In Lcc and Rccsupporting
confidence: 90%
“…PP is a recognised inhibitor of Wnt signalling 15–17 . We confirmed that PP (2 μM) inhibited Wnt signalling using a TCF‐driven‐GFP reporter system in both LIM1899 and SW620 cells (Figure S2).…”
Section: Resultssupporting
confidence: 60%
“…Pyrvinium Pamoate (PP) is a recognized inhibitor of Wnt signaling 16-18 . We confirmed that PP (2µM) inhibited Wnt signaling using a TCF-driven-GFP reporter system in both LIM1899 and SW620 cells (Supplementary Figure 2).…”
Section: Resultsmentioning
confidence: 99%